Pengaruh Firm Size Terhadap Earnings Response Coeffisient (ERC) Dengan Voluntary Disclousure Sebagai Variabel Intervening: Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Daniar Paramita, Ratna Wijayanti (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2012)
Earnings information is the most responded by investors because it provides a description of the company’s performance, but information alone is sometimes not enough profit to serve as the basis for decision making of investors because it is possible the information is biased, to measure the level of profit, can use a variable Earnings Response Coefficient (ERC.) The strong market reaction to earnings information reflected in the high earnings response coefficients (Earnings Response Coefficient) or ERC, if earnings are reported to have a response force (power of response). then that reported earnings quality. The purpose of this study was to identify the effects of direct and indirect size, and earnings response disclousure voluntary coeffisient (ERC) This research examined 20 manufacturing companies listed on the Indonesia Stock Exchange-year period 2005-2009. Statistical methods used to test the hypothesis is Structural Equation Model (SEM) with AMOS version 18. The empirical results of this research: The results of this study proves there is no significant effect of Size with Earnings Response Coefficient (ERC). Similarly, for the effect of the Size to voluntary disclousure have significant positive results. Against the influence of voluntary disclousure to Earning Response Coefficient (ERC) have positive test results significantly. Voluntary disclosure in this study an intervening variable for the indirect effect between the size of Earnings Response Coefficient (ERC). The persistence of earnings as a control variable to the Earnings Response Coefficient (ERC) have no significant relationship.